Sobre olvidos históricos, semblanzas jurídicas y estrategias políticas - Martín, Sebastián (CIAN-Revista de Historia de las Universidades, 2009)
El presente artículo aborda críticamente una reciente publicación sobre la iuspublicística de la Segunda República. Analiza en primer lugar algunas carencias habituales en el estudio del Estado republicano; examina después las debilidades, también frecuentes, cometidas al estudiar las biografías de los juristas españoles contemporáneos; y concluye cuestionando la tesis política sostenida por el autor de la monografía. Palabras clave: Segunda República, Juristas, Ciencia jurídica. On historical oversights, juridical biographical sketches and political strategies. This article critically reviews a recent book on the juridical science publications made during the second Spanish Republic. It begins analyzing certain common deficiencies fallen on when studying that Spanish republican government; it then identifies other also common faults made when studying the biographies of Spanish jurists of that period; and finally questions the political thesis held by the author of that publication. Key words: Second Spanish Republic; jurists; juridical science.